Pengaruh Konseling Menyusui Kepada Pasutri Terhadappengetahuan, Dukungan, Dan Keterampilan Teknik Menyusui (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Percentage of exclusive breastfeeding in Jogja is low at 40.24 % , while the national target is 80 % . Many factors influence the success of exclusive breastfeeding, such as knowlwdge skills and techniques in breasfeeding and husband support. Efforts to increase the percentage is to provide breastfeeding counseling to couples. Husband’s support leads to successful breastfeeding techniques.Objective: The purpose of this study was to determine the effect of breastfeeding on couples counseling to the knowledge, support, and technical skills as well as the correlation of the couples knowledge of breastfeeding in a group of couples.Method: This research is a quasi experiment that assesses “ Effect of Breastfeeding Counseling In A married couple on Knowledge, skills technical Support to Breastfeeding In Public Health Centers of Yogyakarta “, by pretest-posttest control group. Sampling with consecutive sampling techniques in health centers Jetis, Tegalrejo, and Mergangsan, samples are husband and postpartum primiparous mothers who breastfeed their babies which is 60, randomization techniques are used to divide the block into a treatment group and a control group of 30 samples each. Knowledge variables were measured with questionnaires before and after counseling. The variable of husband support in the questionnaire after counseling, while the variable of breastfeeding skills is observed with breasfeeding the checklist before and after counseling. Analysis of the data uses the Wilcoxon, Man Whitney and Spearman Rank.Result: The results showed the score of knowledge and skills in a group of couples and groups prior to the intervention itself not significant (p> 0.05). The median value of knowledge for couples groups is 56.2, skills is 27, 27. The median value of the group itself to the knowledge is 55,0 27.27. The results of the knowledge, and skills after the intervention showed significant differences (p< 0.05). Couples groups is knowledge median value is 92.5, the value of the skills is 100, while the value of the group’s own knowledge 88,7 and skills is 72.72. Median value of knowledge on husband support to couples is (88,8), higher than own group median value (72.2), there is a significant difference (p < 0.05) . There is a husband and wife correlation knowledge which is significant (p